A rapid acquisition GPS receiver based on ultra tightly coupled IMU and GPS - Garcia, Gabriel E. (My University, 2010)
Nowadays, the importance to obtain position in weak signal environments, such as indoors, has increased in order to take a step forward in the greater use of GPS. However, the weak signal environment may include several negative factors such as low signal to noise ratio, signal jamming and interference among others that shall be studied. The present thesis work proposes an open loop approach to deal with the signal dynamics. A Doppler model is proposed in order to remove the dynamics of the incoming GPS signal with the aid of an Inertial Measurement Unit (IMU). The model is broken down into calculating the satellite dynamics, the receiver dynamics and the receiver's oscillator dynamics. An error budget is created in order to see the unpredictable errors and their influence. A bandwidth analysis is also performed in order to analyze the effects of the dynamics in the receiver's phase locked loop (PLL), more specifically in the loop bandwidth. Available measurements from a high tech IMU and a GPS receiver oscillator are analyzed to quantify the time dependant errors. An algorithm to account for the satellite dynamics is proposed with an accuracy Doppler error of ±:0005 Hz. It is shown that the errors from the IMU are dominant in the error budget. However, the receiver dynamics errors are reduced: For a scenario where a vehicle enters a tunnel at 100 km/h and 50 seconds later exits the tunnel with a speed of 28 km/h it is shown that the dynamics of the signal can be reduced from 100 Hz to 6 Hz after implementing the open loop approach. The errors introduced by the oscillator are also shown to be significant with up to 2.58 Hz for L1 GPS signal. These conclusions give arise to the use of lower bandwidth usage in the PLL. Higher signal to noise ratio can be deduced and rapid acquisition and reacquisition of the signal is possible, meaning the GPS signal can be tracked immediately after blockage situations.
Keywords: Fysik; Physical Sciences